Unlawful Act by a Cultivator or Sharecropper Certifying Land that Does Not Belong to Them - Made Ardana; Ni Ketut Wiratny; A. A. Gde Putra Arjawa (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Land registration is an important step in the land administration system to reduce disputes, increase transparency, and ensure compliance with applicable laws and regulations. However, in practice, there are many cases where individuals or groups try to control or claim rights to land that do not belong to them personally, through various unlawful means, including unauthorized certification. This study aims to know and analyze in depth the conditions that must be met in the registration of inherited land and the legal consequences for cultivators/appointees who wrongfully certify land that does not belongs to them. Specifically, this study focuses on the specific legal requirements for registering inherited property and the implications for individuals who attempt to register land illegitimately, highlighting the potential legal repercussions and the need for enforcement of property rights. The findings of this study can be used as a reference for policymakers and legal practitioners.